Peningkatan Kualitas Tidur Lansia dengan Pelatihan Mandiri Hipnotis Lima Jari di Puskesmas Wiradesa Kabupaten Pekalongan - Nugroho, Santoso Tri; Yuniarsih, Sri Mumpuni; Widhowati, Siwi Sri; Suraningsih, Ida (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2024)
Background: The main problem that is often experienced by the elderly is poor sleep quality, this condition can increase the risk of falls resulting in injuries and other health problems that can reduce the quality of life of the elderly. A cheap and easy intervention is needed so that efforts to improve the degree of health of the elderly through improving the quality of sleep of the elderly can be realized, one of which is with Five Finger Hypnosis. The purpose of this Community Service is to identify sleep disorders in the elderly, provide information and self-training Five finger hypnosis as an alternative to overcome sleep disorders in the elderly.  The methods used include coordination with partners to determine the time and location of activities, socialization of 5 Finger Hypnosis and distribution of leaflets. Result: It is known that of the 32 elderly who participated in this activity, the majority (72%) experienced poor sleep quality, the elderly participated in the activity with great enthusiasm and pleasure because they were introduced to alternative interventions to overcome sleep quality disorders that were cheap, easy and effective, and they were also committed to practicing it at home every time they wanted to sleep. Conclusion: 5-finger hypnosis can be used as evidance in an effort to improve the quality of sleep of the elderly in order to improve the quality of life.